2014
DOI: 10.4102/ajlm.v3i2.228
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory system strengthening and quality improvement in Ethiopia

Abstract: Background In 2010, a National Laboratory Strategic Plan was set forth in Ethiopia to strengthen laboratory quality systems and set the stage for laboratory accreditation. As a result, the Strengthening Laboratory Management Toward Accreditation (SLMTA) programme was initiated in 45 Ethiopian laboratories. Objectives This article discusses the implementation of the programme, the findings from the evaluation process and key challenges. Methods The 45 laboratories were divided into two consecutive cohorts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…Six papers presented experiences from a single laboratory 7,10,17,26,28 or a single hospital, 9 14 presented data from two to 45 laboratories within a single African country, 8, 12,–15,18,–22,25,2931 one discussed activities in two Southeast Asian countries, 23 one covered data from four countries in the Caribbean Region 11 and six had a general or global focus. 1,16,23,24,32,33 In total, these studies included detailed information on SLMTA implementation in 211 laboratories in 18 countries.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six papers presented experiences from a single laboratory 7,10,17,26,28 or a single hospital, 9 14 presented data from two to 45 laboratories within a single African country, 8, 12,–15,18,–22,25,2931 one discussed activities in two Southeast Asian countries, 23 one covered data from four countries in the Caribbean Region 11 and six had a general or global focus. 1,16,23,24,32,33 In total, these studies included detailed information on SLMTA implementation in 211 laboratories in 18 countries.…”
Section: Resultsmentioning
confidence: 99%
“…11 Another reported that ‘prior to the introduction of SLMTA, several trainings and quality improvement initiatives had been implemented in hospitals and laboratories in Ethiopia, but little improvement was noted’. 12 In Botswana, there had been ‘slow progress in implementing QMS’, and authors noted that ‘previous training of healthcare workers has focused on general management topics rather than identifying tangible tasks to bring about change, making the training difficult to apply in the laboratory’. 28 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Hiwotu et al detail SLMTA implementation in Ethiopia, documenting substantial improvements to laboratory quality. 9 …”
Section: Introductionmentioning
confidence: 99%